The Body as Interface: New Woman Identity in George Egerton’s “The Regeneration of Two” - Kelso, Charlotte (Australasian Journal of Victorian Studies, 2020)
This article examines George Egerton’s New Woman short story, “The Regeneration of Two”, from her 1894 collection Discords. Through the physical, mental, and social transformation of her heroine, Fruen, Egerton critiques normative femininity and the limited narratives that women are afforded within Victorian fiction, using the female body as an interface for the exploration and transformation of Victorian femininity and identity. In the text, the languages of dress and self-fashioning are used to explore identity and subjectivity, while also critiquing the conflicting expectations of women and the artificial performativity of the angelic feminine ideal. Fruen’s transformation into a “whole woman” (Egerton, “Regeneration” 252) through the rejection of her corset and the literal growth of her body, as well as her developed social awareness of women’s position, offer a distinctly ‘New Woman’ mode of femininity based on strength and individual agency. In Fruen’s growth towards self-actualisation, her body acts as an interface of not only her own negotiation of identity and its signifiers, but also of Egerton’s exploration of women’s narratives and the systems and conventions that create and uphold limiting ideals of femininity.